Gendered priorities for ‘improved’ sanitation: insights from Kisumu Kenya - Jewitt, Sarah; Ryley, Harriet (2015)
This paper explores how official concepts of ‘improved’ sanitation often fail to reflect the priorities of female users. As the health benefits associated with improved sanitation cannot be fully realised until all potential user groups habitually utilize it, specific user preferences/constraints need to be better understood and catered for. Drawing on empirical work in nine schools in Kisumu, Kenya, attention is focused on gendered sanitation priorities including menstrual hygiene management, gender-based violence and broader safety, privacy and dignity issues associated with accessing and using sanitation facilities.